CHILD COMIC DEVELOPMENT WITH THE THEMES OF PREVENTION COVID-19: VALIDATION ANALYSIS - Munjiatun, Munjiatun; Guslinda, Guslinda; Kurniaman, Otang; Noviana, Eddy; Ramadhan, Muhammad (Metodik Didaktik : Jurnal Pendidikan Ke-SD-an, 2021)
The purpose of this study is to describe the feasibility of making children's comics with the theme of preventing covid 19. This research is a research and development study. This research method is a research aimed at producing certain products and testing the effectiveness of these products. The method used by researchers this time is the model developed by Thiagarajan, namely the Four-D model. The Four-D development model consists of 4 main stages, namely: define, design, develop and disseminate (Sugiyono, 2015). The results of this study are seen from the results of the validation of the material with a value of 86% in the proper category, while the results of the validation of the media experts with the results of the assessment of 87.08% with the conclusion of this study that this comic media is suitable for children to use and read.